'It's small steps, but that leads to bigger changes': evaluation of a nurture group intervention. Issue 4 (2nd October 2017) - Vincent, Kerry
ABSTRACT: This article presents the results of a small-scale research project that aimed to evaluate the effectiveness of a part-time nurture group recently established in one primary school. Qualitative interviews were used to gather staff, pupil and parental perceptions about the nurture group. These focused not only on what difference the nurture group was making to the pupils concerned but also on views about what factors contributed to noted changes. All stakeholder groups identified areas of development for nurture group pupils. These included improved social skills, growth in personal confidence, greater engagement with academic tasks and fewer incidences of undesirable behaviour. The evidence suggests that the nurture group offered an effective way of supporting the social, emotional and behavioural skills of a group of 'at-risk' pupils. Nine practices thought to be important in achieving these outcomes are highlighted.